Preliminary Investigation Of Gray Coded Mquadrature Amplitude Modulation In Orthogonal Frequency Division Multiplexing Over Additive White Gaussian Noise Channel - Noordin, Nor K.; M. Ali, Borhanuddin; Jamuar, S. S.; Abdul Rahman, Tharek; Ismail, Mahamod (Penerbit UTM Press, 2004)
In this paper, we investigate the performance of Gray encoding M-Quadrature Amplitude Modulation (QAM) schemes in Orthogonal Frequency Division Multiplexing (OFDM) transmission over added white Gaussian noise (AWGN) channel. Gray-coded QAM with 1 to 8-bit symbol corresponding to 2 to 256-QAM respectively is generated and fed into OFDM transmission system. Performance in terms of bit error rate (BER) is presented against OFDM fast Fourier transform (FFT) size, subcarrier number, length of cyclic prefix, and tolerance to signal to noise ratio of the channel. Preliminary results show that only 16 and lower level-QAM are attractive to achieve a bit error rate (BER) of 10–3 with signal to noise ratio of at least 20 dB. The higher level QAM such as 256-QAM scheme will require at least a SNR of 50 db to achieve similar outcome. The study also shows that the performance of the system is not affected by the number of fft-points used, or the length of cyclic prefix inserted to the transmitted signal. However, the number of subcarriers does depend on the level of QAM used at a given SNR value.